Biotic interactions contribute more than environmental factors and geographic distance to biogeographic patterns of soil prokaryotic and fungal communities - Liu, Yu; Ding, Chengxiang; Li, Xingfu; Su, Derong; He, Jing (Frontiers in Microbiology, 2023)
Recent studies have shown distinct soil microbial assembly patterns across taxonomic types, habitat types and regions, but little is known about which factors play a dominant role in soil microbial communities. To bridge this gap, we compared the differences in microbial diversity and community composition across two taxonomic types (prokaryotes and fungi), two habitat types (Artemisia and Poaceae) and three geographic regions in the arid ecosystem of northwest China. To determine the main driving factors shaping the prokaryotic and fungal community assembly, we carried out diverse analyses including null model, machine learning and variance partitioning analysis etc. The results showed that the community assembly mechanism differed more between taxonomic types than habitat types and geographic regions. The predominant driving factor of community assembly was biotic interactions between microorganisms, followed by environmental filtering and dispersal limitation. Network vertex, positive cohesion and negative cohesion showed the most significant correlations with prokaryotic and fungal diversity and community dissimilarity. Salinity was the major environmental variable structuring the prokaryotic community. Although prokaryotic and fungal communities were jointly regulated by the three factors, the effects of biotic interactions and environmental variables (both are deterministic processes) on the community structure of prokaryotes were stronger than that of fungi. The null model revealed that deterministic processes dominated the community assembly of prokaryotes, whereas fungal community assembly was more stochastic. Taken together, these findings unravel the predominant role governing microbial community assembly across taxonomic types, habitat types and geographic regions and highlight the significance of considering biotic interactions in studies of assembly mechanisms.